Prevalence of Sacroiliac Joint Pain in Pregnant Women of Lahore City - Hira Shafiq, Sana Tauqeer, Fatima Younas, Sobia Ghafoor, Momna Asghar, Maryam Azam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bio-mechanical changes during pregnancy impose postural deviation, its leading sacroiliac joint pain, or this pain increase with advancing pregnancy or interface the daily activities or sleep. Aim: To determine the prevalence of sacroiliac joint pain. Methods: This Cross sectional study was conducted at Kannan Physiotherapy and Spine Clinic Lahore, Pakistan. Convenient sampling non-probability sampling method was used, PGQ questionnaire or clinical tests are used to diagnose the sacroiliac joint pain. Results: Total pregnant women are 196, There sum of all activity or sum value divided by 75 or multiply by 100, mean 37.30; std. deviation 18.239; minimum 0; maximum 85.(the population of 1000 pregnant women were considered of which 196(19.6%) said they feel pain while 804(80.4%) said they didn’t feel pain or pain increase with trimester. Conclusion: The study concluded that pregnant women are at mild to moderate rate of developing sacroiliac joint pain due to repetitive bad posture or heavy weight during pregnancy. Keywords: Pregnancy, Sacroiliac joint pain, Pelvic girdle questionnaire, clinical test.